Polyarylate based thin film composite (TFC) membranes: effects of coating parameters, gutter layer, and intrinsic material properties - Chendake, Yogesh J.; Bhole, Yogesh S.; Lohokare, Harshada R.; Kharul, Ulhas K. (Separation Science and Technology, 2010)
Investigations in thin film composite (TFC) membrane formation with polyacrylonitrile ultrafiltration membrane as a support and three polyarylates with sequentially increased polarity are reported. Effects of TFC membrane preparation parameters viz., concentration of the coating solution, dip time, presence of solvent in pores of UF membrane support, and presence of the gutter layer were examined towards the formation of the selective skin layer, which was assessed by gas permeation analysis. TFC membranes prepared using dimethyl bisphenol-A based polyarylate exhibited similar to 3 orders of magnitude higher permeability and comparable selectivity as that of its dense membrane.
Keywords: Gas permeation; gutter layer; polarity; polyarylates; TFC membrane

Pt-MoOx-carbon nanotube redox couple based electrocatalyst as a potential partner with polybenzimidazole membrane for high temperature polymer electrolyte membrane fuel cell applications - Vellacheri, Ranjith; Unni, SreeKuttan M.; Nahire, Sandip; Kharul, Ulhas K.; Kurungot, Sreekumar (Electrochimica Acta, 2010)
A redox couple based electrocatalyst comprising of Pt-Multi Wall Carbon NanoTube (Pt-MWCNT) promoted with molybdenum oxide (MoOx, 2 < x < 3) nanoparticles was prepared. The objective was to effectively organize the Pt-MoOx interface on the smooth MWCNT surface to overcome the practical difficulties associated with establishing such interface with Pt dispersed on carbon morphologies possessing surface irregularities. The present study revealed the importance of stringent controlling of the additive level for maintaining a balanced bifunctional behavior of the catalyst combination through the synergistic effects by the components and the need of a proton conducting membrane operable at high temperature to get better output from the Polymer Electrolyte Membrane Fuel Cell (PEMFC) systems. An indigenously developed polybenzimidazole (PBI) membrane was used to fabricate a membrane electrode assembly (MEA) as it can be operated at higher temperatures compared to that of Nafion membranes. MoOx additive level was carefully controlled by monitoring the active Pt area by cyclic voltammetry. All prepared electrocatalysts were characterized by using HRTEM, XRD and XPS to get information on dispersion and morphology, crystalinity and oxidation state of different elements, respectively. The system prepared with 5% MoOx addition with respect to Pt (hereafter Pt-MoOx(5%)-MWCNT) displayed balanced active Pt area and excellent oxygen reduction reaction (ORR) and methanol oxidation reaction (MOR) activities. Rotating Disk Electrode (ROE) system was extensively utilized to understand the ORR kinetics and the favorable role of MoOx as the promoter in the reaction. The kinetic current (j(k)) measured at 0.02 V vs. Hg/Hg2SO4 electrode from the Koutecky-Levich plots was 9 times higher and the apparent activation energy during single cell evaluation was 27 kJ/mol lower for the MoOx promoted system, compared to the system without the additive. A higher operating temperature significantly favored the cell performance by a combined effect of enhancement in proton conductivity of the PBI membrane and possible kinetic benefit by the well postulated oxygen spill over effect by the MoOx type systems in some combinations involving such systems. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Methanol oxidation reaction; MWCNT; oxygen reduction reaction; PBI membrane; PEMFC

Poly(acrylonitrile) based ultrafiltration membranes: optimization of preparation parameters - Lohokare, Harshada R.; Bhole, Yogesh S.; Taralkar, Suyog; Kharul, Ulhas K. (Desalination, 2011)
Supported ultrafiltration (UF) membranes based on poly(acrylonitrile) were prepared while varying crucial parameters responsible for controlling membrane porosity, viz.; polymer concentration, solvent and additives in the dope solution. Insight into membrane porosity and morphology was obtained by water flux, solute rejection, bubble point, pore size distribution, SEM and AFM analyses. It was found that merely increasing polymer concentration does not necessarily reduce pore size of membranes. Among four solvents used for the dope solution preparation, N-methyl pyrrolidone was found to offer membranes with optimal combination of flux and rejection of various solutes. Some of the PAN(17) (17% w/w PAN concentration in the dope solution) membranes prepared using organic acid as the additive (citric acid, tartaric acid or maleic acid) offered 1.2-1.7 times higher flux than the membrane prepared using inorganic salt, ZnCl2 as an additive. The porosity of PAN(17) membrane prepared using CA as an additive was larger as compared to membrane prepared using ZnCl2 as an additive. Atomic force microscopy (AFM) analysis of this membrane exhibited higher surface roughness as compared to the ZnCl2 based membrane. Both these membranes exhibited bacteria (E. Coli) log reduction value (LRV) of at least 6; depicting applicability of these membrane for water disinfection. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Additive; Bacteria rejection; Poly(acrylonitrile); Pore size distribution; Ultrafiltration

Polybenzimidazoles based on 3,3 `-diaminobenzidine and aliphatic dicarboxylic acids: synthesis and evaluation of physicochemical properties toward their applicability as proton exchange and gas separation membrane material - Bhavsar, Rupesh S.; Nahire, Sandip B.; Kale, Mrunali S.; Patil, Shubhangi G.; Aher, Pradnya P.; Bhavsar, Ritesh A.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2011)
A series of aromatic-aliphatic polybenzimidazoles (PBIs) based on 3,3'-diaminobenzidine (DAB) and aliphatic dicarboxylic acid with incremental -CH2- groups were synthesized. Optimization of synthesis parameters and evaluation of physicochemical properties are requisite for PBI applicability as the proton exchange membrane (PEM) and gas separation membrane materials are reported. It was found that though all these PBIs exhibited high thermal, mechanical, and oxidative stability, effect of added flexibility on physical properties is not monotonous. Membranes were prepared by solution casting as well as phase-inversion method. The later types of membranes exhibited much higher H3PO4 content than its doping achieved in the solution casted membranes. These PBIs possess low hydrogen and helium permeability than that of conventional PBI. This low permeability, along with their excellent oxidative stability indicated that they can be promising PEM materials. Their CO2-sorption analysis revealed that PBI6 based on suberic acid possesses appreciable CO2 sorption. (C) 2010 Wiley Periodicals, Inc. J Appl Polym Sci 120: 1090-1099, 2011
Keywords: Gas permeation; mechanical properties; membranes; oxidative stability; polybenzimidazoles

Polybenzimidazole mediated N-doping along the inner and outer surfaces of a carbon nanofiber and its oxygen reduction properties - Balan, Beena K.; Manissery, Aiswarya Padinhare; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
Nitrogen-doped (N-doped) hollow carbon nanofiber (CNF) was synthesized by incorporating a nitrogen containing polymer precursor, polybenzimidazole (PBI-BuI), in the inner cavity as well as on the outer walls of the CNF, followed by a high temperature treatment. PBI-BuI incorporation along the inner and outer surface of the CNF was accomplished by synthesizing a low molecular weight polymer by tuning the synthetic parameters. The solution concentration of the PBI-BuI is also varied to facilitate its entry into the CNF by capillary action. The high temperature treatment (700-1000 degrees C) of the resulting CNF-PBI material decomposes the polymer and induces N-doping along the inner and outer surfaces of the CNF. The initial PBI-BuI content and the annealing temperature are also systematically varied to choose the right combination of starting precursors and heat-treatment conditions. Detailed X-ray photoelectron spectroscopy analysis of the samples shows that pyridinic-type nitrogen is the major component in all the samples. Electrochemical characterizations of this material using cyclic voltammetry, rotating disc electrode studies and durability analysis demonstrated that this material can act as a metal-free oxygen reduction electrocatalyst with improved oxygen reduction kinetics and stability. It is also revealed that the onset potential, limiting current density, number of transferred electrons, etc. have a strong dependence on the annealing temperature.

Polymeric ionic liquids (PILs): effect of anion variation on their CO2 sorption - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2012)
A series of polymeric ionic liquids (PILs) based on poly(diallyldimethylammonium chloride), P[DADMA][Cl] as a precursor was investigated by varying anions categorized into carboxylates, sulphonates and inorganic type. For the exchange of chloride from P[DADMA][Cl] by another anion, silver salt of the corresponding anion was preferred. Obtained PILs were investigated for physical properties which are anticipated to affect gas sorption. PILs possessing carboxylate (especially acetate) anion exhibited attractive CO2 sorption capacity as well as sorption selectivity over H-2 and N-2, in Comparison to Other two Categories. PIL with acetate anion, P[DADMA][Ac] possessed appreciable CO2 sorption coupled with high selectivity (S-CO2/S-N2 = 114.3). This crucial finding from this series of PILs was further substantiated by making PIL based on poly(vinylbenzyltrimethylammonium chloride), P[VBTMA][Cl] as a precursor. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; CO2 sorption; Polymeric ionic liquid

PBI-BuI and PAN-PSSALi based UF membranes: effects of solute and membrane surface interactions on rejection and flux - Bhagat, Deepti G.; Mule, Bhavana; Mandlekar, Neeraj; Pandare, Kiran; Kharul, Ulhas K. (Desalination, 2014)
Ultrafiltration membrane using tert-butylpolybenzimidazole (PBI-BuI) was prepared and characterized for flux and rejection performance using Gel Permeation Chromatography (GPC). Polyethylene glycol (PEG) and polyethylene oxide (PEO) with different molecular weights were used as the solutes. While using feed solution containing mixture of PEGs, higher rejection was observed than using individual PEG. The water flux of PBI-BuI membrane after passing individual PEG solutions showed considerable (similar to 36%) reduction, which could be attributable to the PEG adsorption on the membrane pore surface. PEG adsorption was further substantiated by SEM, IR and TGA. The amphoteric nature of PBI-BuI could cause H-bonding between membrane surface and PEG molecules, leading to PEG adsorption on the membrane and pore surface. To ascertain this postulation, a study with PAN-PSSALi (which does not contain H-bonding) based UF membrane containing negatively charged -SO3- group was done. It was found that PEG adsorption in this case is not as predominant as in earlier case. This membrane showed marginal reduction in water flux of 8%, vis-a-vis 36% reduction shown by PBI-BuI based membrane. This indicated that H-bonding present in PBI-BuI is mainly responsible for the PEG adsorption on its membrane and pore surface, in spite of PEG being a neutral molecule. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Gel permeation chromatography; Polybenzimidazole; Rejection; Solute adsorption; Ultrafiltration

Polybenzimidazole based film forming polymeric ionic liquids: synthesis and effects of cation-anion variation on their physical properties - Bhavsar, Rupesh S.; Kumbharkar, Santosh C.; Rewar, Anita S.; Kharul, Ulhas K. (Polymer Chemistry, 2014)
Polymeric ionic liquids (PILs) are gaining wide attention due to their tunable properties and applicability in various upcoming areas, including membranes for CO2 separation. The known methodologies yield PILs that are difficult to convert into film form. The present work investigates a synthetic approach for obtaining PILs based on a strong film forming with a fully aromatic rigid backbone while incorporating ionic liquid character in it. Three structurally different polybenzimidazoles (PBI-I, PBI-BuI and ABPBI) were N-quaternized by a methyl group, followed by iodide exchange with various promising anions. The extent of iodide exchange by another anion was high enough (>94% in most cases). Most of the resulting PILs with various anions offer mechanically strong films, with the exception of those based on acetate and benzoate as an anion. Although the base PBI has excellent film forming ability, this result conveyed the role of anion in governing the film forming ability of the PIL. Salient features of this methodology include a fully aromatic polycation backbone, wide structural tunability (by virtue of variation not only of the anion/cation, but also with N-substituent) and introducing two IL characters per repeat unit of a PIL (except for PILs based on ABPBI). Attempted PIL structural variations showed diverse property variations in bulk and surface properties (solvent solubility, contact angle, water sorption, thermal stability, polyelectrolyte behaviour, CO2 sorption and ionic conductivity). Mechanical properties of film forming PILs exhibited high enough tensile strength, conveying their applicability as membrane materials.

Polybenzimidazole based polymeric ionic liquids (PILs): effects of controlled degree of N-quaternization on physical and gas permeation properties - Rewar, Anita S.; Bhavsar, Rupesh S.; Sreekumar, K.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric ionic liquids (PILs) are gaining increasing attention as potential membrane materials to be employed for CO2 separation. With a goal to improve gas permeability, this work presents a series of film forming PlLs obtained by controlled degree of N-quaternization (DQ) of PBI-BuI using a bulky 4-tertbutylbenzyl group. Concurrent effects of variation in ionic content and bulky group substitution were analyzed for physical and gas permeation properties of the resulting PILs. Attempted structural variations leading to simultaneous increments in ionic content and bulky groups offered amorphous polymers with acceptable thermal stability and non-monotonous chain packing density. Enhancement in pure gas permeability coupled with appreciable selectivity for various gas pairs was in accordance with the packing density variations in the series. Gas permeability showed maxima at DQ of just 13%. This conveyed that effects of bulky group substitution in retarding chain packing are overcome by attractive ionic interactions at much lower DQ in these PILs ionic interactions are thus more predominant in governing chain packing and gas permeation properties. These PILs possessed 3.3-20 times higher CO2 permeability in comparison to their parent PBI-BuI, without a significant loss in selectivity. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Degree of quaternization; Gas permeation; Polybenzimidazole; Polymeric ionic liquid

Polybenzimidazole-based polymeric ionic liquids (PILs): effects of `substitution asymmetry' on CO2 permeation properties - Shaligram, Sayali V.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric Ionic Liquids (PILs) are being considered as promising membrane materials for CO2 separation. Present work aims at investigating effects substitution asymmetry on imidazole moiety of two structurally different polybenzimidazoles (PBI-BuI and PBI-HFA) on physical, gas sorption and transport properties of the resulting film forming PILs possessing symmetric substitution, while keeping one of the N-substituent as methyl group. PILs were obtained with high degree of substitution. The halide anion of these PILs was exchanged with BF4-, Tf-2(N) over bar and HF (B) over bar anions. Effects of substituents, cationic backbone and type of anions on gas permeation properties of PILs using pure gases (He, H-2, N-2 and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. Combination of typical ionic liquid character (effective towards enhancing CO2 sorption) and looser chain packing (ease in gas diffusion) offered improved CO2 permeation characteristics. As an outcome, some of the PILs exhibited higher CO2 permeation than that of hydrogen, typically known as `reverse selectivity'. These asymmetrically substituted PILs enhanced not only the gas permeability, but also selectivity than their symmetrically substituted counterparts. (C) 2015 Elsevier B.V. All rights reserved.

Pore surface engineering in porous, chemically stable covalent organic frameworks for water adsorption - Biswal, Bishnu P.; Kandambeth, Sharath; Chandra, Suman; Shinde, Digambar Balaji; Bera, Saibal; Karak, Suvendu; Garai, Bikash; Kharul, Ulhas K.; Banerjee, Rahul (Journal of Materials Chemistry A, 2015)
Herein, we have explored the possibility of a class of covalent organic frameworks (COFs) as water adsorbing materials. We have selected, synthesized 12 chemically stable functionalized Schiff base COFs and thoroughly studied their water uptake behaviour. Further, a deep understanding was developed with these COFs towards the effects of condensation pressure of water and hydrophilic/hydrophobic groups present in the COF pores on water absorption capacity and ultimately, their recyclability. Among all reported COFs, TpPa-1 shows the highest water uptake of 30 wt% (368 cm(3) g(-1); 17 mmol g(-1)) at P/P-0 = 0.3, which is also comparable with the recently reported carbon materials and few well known MOFs. This study also reveals that the overall water uptake of COFs can be tuned systematically based on chemical functionality and pore size in a wider window of relative pressures.

Polybenzimidazole based polymeric ionic liquids possessing partial ionic character: effects of anion exchange on their gas permeation properties - Rewar, Anita S.; Shaligram, Sayali V.; Kharul, Ulhas K. (Journal of Membrane Science, 2016)
Polymeric ionic liquids (PILs) are emerging as promising membrane materials for CO2 separation. Present work is in continuation with our earlier efforts on evaluating gas permeation properties (especially, CO2) of film forming PILs based on polybenzimidazoles and efforts towards improving their permeability by structural tuning. This work specifically aims at evaluating effect of anion variation in chosen PILs possessing partial N-quaternization of imidazole moiety of PBI-Bul. Three anions (viz., Tf2N-, BF4- and Ac-) were chosen for the bromide exchange of two PILs, viz., [TBzPBI-Bul][Br](10) and [TBzPBI-Bul][Br](18), possessing degree of PEI N-quaternization (DQ) as 10 and 18%, respectively. Concurrent effects of variation in anion and DQ were analyzed in terms of physical and gas permeation properties of the resulting PILs. All of them possessed amorphous nature, adequate thermal stability ( >= 250 degrees C) and solvent solubility, which are primary requisites towards their applicability as a membrane material. PILs possessing BF4- anion exhibited improved CO2 permeability coefficient as well as its permselectivity over CH4 and N-2, in comparison to their counterparts with other anions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Anion exchange; Gas separation; Polybenzimidazole; Polymeric ionic liquids (PILs)

Preparation and investigations of ABPBI membrane for HT-PEMFC by immersion precipitation method - Chaudhari, Harshal D.; Illathvalappil, Rajith; Kurungot, Sreekumar; Kharul, Ulhas K. (Journal of Membrane Science, 2018)
Poly(2,5-benzimidazole) (ABPBI) membranes were prepared by an easy and benign 'immersion precipitation' method; alleviating drawbacks of conventional solution casting method involving evaporation of the corrosive solvent. The importance of varying inherent viscosity on the properties of resulting membranes was investigated. The porous membranes formed by immersion precipitation method were analyzed for basic properties (water flux, porosity and dimensional analysis). Since the dense structure is required for their applicability for a fuel cell, through-porosity of the formed membranes was successfully eliminated using a unique shrinkage (similar to 50%) property of ABPBI, initially, at 60 degrees C followed by at higher temperature. The correlation of membranes annealing temperature with the mechanical properties, phosphoric acid doping and proton conductivity was established. The present membranes exhibited high doping level (5.1 mol/RU), proton conductivity (0.083 S cm(-1)) and fuel cell performance. For comparison, solution casted membranes were prepared and analyzed. The OCP (0.91 V) and max power density (766mWcm(-2)) are quite promising features of this new type of membranes.

PPO-ZIF MMMs possessing metal-polymer interactions for propane/ propylene separation - Kunjattu, H. Shebeeb; Kharul, Ulhas K. (Journal of Membrane Science, 2023)
An assertive formation of ZIF-based mixed matrix membranes (MMMs) with polyphenylene oxide (PPO), a high permeability polymer as a host, is presented. The interfacial interactions between the filler particles and polymer matrix are established by DSC and XPS analyses. The ZIF loading could be achieved up to 40% without hampering the stability of the resulting MMMs. These membranes were evaluated for pure gas permeability, specifically aiming at C3H6/C3H8 separation, a highly desired application in industry. The ZIF-PPO hybrids display promising pure gas as well as mixed gas permeation performance. The 40% ZIF-8 and ZIF-67 loaded membrane display promising C3H6/C3H8 selectivity of 27.5 and 25, with a permeability of 12 and 13 barrer, respectively. The enhanced selectivity is attributed to the absence of defects eliminated due to metal-polymer interactions. The permeation study of a 30% ZIF-8 loaded membrane while varying transmembrane pressure and long-time exposure (150 h) of propylene at 60 psi indicated the excellent stability of the membrane. The sorption analysis further confirmed the molecular sieving characteristics of the ZIF@PPO MMMs. The mixed gas permeation performance showed promising results of high permeability as well as maintaining selectivity over a wide range of compositions.
Keywords: Interfacial interactions; Mixed matrix membrane; Olefin-paraffin separation; poly(phenyleneoxide); Zeolitic imidazole framework

Poly(2,5-Benzimidazole) as a membrane material for solvent dehydration: effect of bound methanesulfonic acid - Alladi, Lavanya; Lele, Ashish K.; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2025)
Towards addressing issues of solvent stability of polymeric membrane materials for pervaporation (PV), this work investigates thermochemically robust poly(2,5-benzimidazole) (ABPBI) bound with methane sulfonic acid (MSA) for solvent dehydration, for the first time to our knowledge. Phase inversion membranes with and without bound-MSA were prepared, thermally treated at different temperatures up to 350 degrees C, and analyzed for physical and pervaporation properties. The physical characterizations (FTIR, WAXD, TGA, XPS, SEM, and EDX) and sorption analysis were performed using flat sheet membranes, whereas hollow fiber membranes were used for the pervaporation analysis with chosen solvents (alcohols and two polar aprotic solvents). Physical characterizations established the presence of MSA and the nonporous, dense nature of membranes, irrespective of their treatment temperatures. The sorption of pure solvents in the membrane is primarily affected by thermal treatment of the membranes. The pervaporation analysis was performed using different solvent: Water feed compositions. Using 85:15 as the feed, the average separation factors for dehydration of isopropanol, acetonitrile, and N,N-dimethylformamide (DMF) were 393, 213, and 185, respectively, with an appreciable ``pervaporation separation index.'' The long-term membrane performance till 360 h was analyzed to shed light on practical applicability.
Keywords: membranes; separation techniques; synthesis and processing techniques

Poly(2,5-Benzimidazole)-based flat sheet membranes: investigating effects of dope solvent and membrane heat treatment on forward osmosis and acid enrichment performances - Somkuwar, Nitin C.; Thorat, Nitin M.; Ambade, Ashootosh; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2026)
The present work investigates two methods for preparing defect-free, symmetric membranes of the thermochemically robust polymer, poly(2,5-benzimidazole) (commonly known as ABPBI) for forward osmosis (FO), a growing technology for niche separations. The obtained polymer and membranes were analyzed for physical properties of significance. The FO analysis was performed using three salt solutions, viz., sodium chloride (NaCl), magnesium chloride (MgCl2), and sodium sulfate (Na2SO4). The effects of casting methodology (solvents present in the dope), membrane heat treatment, draw solution concentration, long-duration analysis, and FO-assisted enrichment of organic acids were evaluated. Some of the membranes exhibited extremely low reverse salt flux (RSF), which conveys the novelty of these membranes. Some of these membranes were analyzed using a high draw solution (DS) concentration (4 mol L-1) to enhance water flux and further employed to enrich organic acids. The aqueous acetic and methacrylic acid concentrations were enriched from 4.89 and 2.93 mol L-1 to 11.88 and 10.01 mol L-1, respectively. These results demonstrate an unmet need of concentrating methacrylic acid (a temperature-sensitive compound possessing a double bond). The present work demonstrates the potentials of ABPBI-based symmetric, thin membranes for FO and their industrial applicability for the first time.
Keywords: Applications; membranes; separation techniques